Agreement between the 2009 STOPP Criteria and the 2003 Beers Criteria at the time of hospital admission - María Muñoz García; Eva Delgado Silveira; Sagrario Martín-Aragón Álvarez; Teresa Bermejo Vicedo; Alfonso José Cruz-Jentoft (Elsevier, 2016)
Potentially inappropriate prescription in elderly patients can be evaluated by different methods. The STOPP Criteria and Beers Criteria stand out among the explicit criteria most widely used. Objective: The main objective of this study is to identify the agreement in the detection of potentially inappropriate prescribing between the STOPP criteria and the Beers Criteria, in elderly patients assessed at the time of hospital admission. Method: An observational retrospective study was designed in order to estimate the prevalence of potentially inappropriate prescription in the habitual treatment before admission, and to compare the agreement in detection capability between the 2003 Beers Criteria and the 2009 STOPP Criteria, in >70-yearold patients with an emergency hospital admission. There was also a specific analysis of the prescription of first-generation antihistamines, tricyclic antidepressants, benzodiazepines, and selective serotonin reuptake inhibitors, which are considered drugs with irregular management and potential toxicity. Results: The total prevalence of patients with a potentially inappropriate prescription was 23.8% using the Beers Criteria and 33.3% using the STOPP Criteria. There was a low level of agreement between both questionnaires. First-generation antihistamines (Beers) and pharmacological duplication (STOPP J) were the criteria most frequently found. There were differences in the prevalence of potentially inappropriate prescription in the four pharmacological groups selected; and in all cases, detection by Beers Criteria was superior. Conclusion: There is no agreement between the STOPP Criteria and the Beers Criteria regarding the detection of patients with potentially inappropriate prescribing at the time of hospital admission.